Management of veno‐occlusive disease: the multidisciplinary approach to care. (2nd February 2017) - Wallhult, Elisabeth; Kenyon, Michelle; Liptrott, Sarah; Mank, Arno; Ní Chonghaile, Mairéad; Babic, Aleksandra; Bijkerk, Jacobine; Bompoint, Caroline; Corbacioglu, Selim; de Weijer, Roel; Fink, Claudia; Marktel, Sarah; et al.
Abstract: Although it is considered a relatively rare disorder, veno‐occlusive disease (VOD) is one of the main causes of overall, non‐relapse mortality associated with haematopoietic stem cell transplantation (HSCT). This article, based on the consensus opinion of haemato‐oncology nurses, haemato‐oncologists and pharmacists from both adult and paediatric services at the VOD International Multi‐Disciplinary Advisory Board at the European Society for Blood and Marrow Transplantation (EBMT) meeting, Istanbul, 2015, aims to explore the multidisciplinary approach to care for the management of VOD, with an emphasis on current challenges in this area. The careful monitoring of HSCT patients allows early detection of the symptoms associated with VOD and timely treatment, ultimately improving patient outcomes. As part of a multidisciplinary team, nurses have an essential role to play, from pretransplant assessment to medical management and overall care of the patient. Physicians and pharmacists have a responsibility to facilitate education and training so that nurses can work effectively within that team.